O-linked N-acetylglucosamine glycosylation of p65 aggravated the inflammation in both fibroblast-like synoviocytes stimulated by tumor necrosis factor-α and mice with collagen induced arthritis. Issue 1 (December 2015) - Kim, Han; Lee, Sang Won; Mun, Chin; Yoon, Ji; Pai, Jaeyoung; Shin, Injae; Park, Yong Beom; Lee, Soo Kon; Cho, Jin
Abstract Introduction We investigated the inflammatory potential of O-linked N-acetylglucosamine glycosylation (O-GlcNAcylation) of p65 in rheumatoid arthritis (RA). Methods Fibroblast-like synoviocytes (FLS) and MH7A cells were treated with synthetic ThiaMet-G (200 μM), an O-GlcNAcase (OGA) inhibitor, followed by tumor necrosis factor (TNF)-α (10 μg/mL). Proliferation of synovial cells was measured by MTT assay, and the levels of mRNAs encoding pro-inflammatory molecules were quantitated by RT-PCR. The nuclear localization of O-GlcNAcylated of p65 and its DNA binding affinity and transcriptional activity were assessed. The severity assessment of arthritis and a histopathological examination were done in mice with collagen induced arthritis (CIA). ThiaMet-G (20 mg/kg) intraperitoneal injection was done every other day for 26 days. Fluorescence-activated cell sorting (FACS) analysis of T cells was performed. Results Hyper-O-GlcNAcylation increased the proliferation and mRNA expression of pro-inflammatory genes in synoviocytes stimulated by TNF-α. Moreover, O-GlcNAcylation of p65 enhanced its proportion of nuclear localization, DNA binding affinity and transcriptional activity. In CIA mice, ThiaMet-G significantly aggravated the severity of arthritis clinically and histologically, and it also increased CD4 + IFN-γ + T cells and CD4 + IL-17+ T cells. Conclusions O-GlcNAcylation of p65 increased the effects of TNF-α-mediated inflammation bothin vitro (in synovial cells) andin vivo (in mice with CIA).